2016
DOI: 10.1002/bmb.20972
|View full text |Cite
|
Sign up to set email alerts
|

Vertical integration of biochemistry and clinical medicine using a near‐peer learning model

Abstract: Vertical integration has been extensively implemented across medical school curricula but has not been widely attempted in the field of biochemistry. We describe a novel curricular innovation in which a near-peer learning model was used to implement vertical integration in our medical school biochemistry course. Senior medical students developed and facilitated a case-based small group session for first year biochemistry students. Students were surveyed before and after the session on their attitudes about bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Integration of basic sciences into clinical years might involve formally revisiting basic science courses; 6 examples involve anatomical reviews or hands‐on activities 19 – 22 . Another approach utilizes senior students as authors of case‐based small group sessions for first‐year students in biochemistry 23 …”
Section: Discussionmentioning
confidence: 99%
“…Integration of basic sciences into clinical years might involve formally revisiting basic science courses; 6 examples involve anatomical reviews or hands‐on activities 19 – 22 . Another approach utilizes senior students as authors of case‐based small group sessions for first‐year students in biochemistry 23 …”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that teaching methods of IBL can improve the teaching quality and facilitate the students to accept the professional knowledge. Recent studies used vertical integration in a clinical setting have also announced similar positive responses from the students . Malau‐Aduli et al .…”
Section: Resultsmentioning
confidence: 75%
“…Chinese medical students could not benefit from the detailed basic science learning of the preclinical years to better understanding, synthesis, and analysis of a patient's clinical manifestations and its correlationship with pathophysiology and anatomical localization . It is important to integrate the basic medical knowledge, such as biochemistry into undergraduate education, and then finally turn into the field of clinical practice .…”
Section: Introductionmentioning
confidence: 99%
“…Methods of introducing clinical topics within basic science courses have previously included case-based clinical sessions [6] and instruction in clinical skills like ultrasonography [7]. Basic science has also been integrated into instruction on clinical topics [8], into clerkships [9], and into anatomy in the context of histologic skin findings [10].…”
Section: Discussionmentioning
confidence: 99%